The Effectiveness of Videos Tutorial to Facilities of Make up Face for Light Mental Retardation Children - Yolanda Syafda; Armaini Armaini (EDUTEC : Journal of Education And Technology, 2019)
This research discusses makeup skills for mildly mentally retarded children. This research is experimental research. The purpose of this study is to prove an effective video tutorial used in improving makeup skills for mildly mentally retarded children.This type of research is an experimental method in the form of pre-experimental with the type of one group pretest-posttest design. The subjects of this study were 5 mild retarded children in SLB N 2 Padang. This study consists of several stages, namely the first stage of the pretest to determine the initial condition of the ability to apply makeup, then given treatment using a video tutorial and continued by providing posttest processed and compared using the Wilcoxon Rank Task test. From the results of the study, the data obtained on average at the time of the pretest is 34.00 while for the posttest there is an increase that is to 85.80. More scientific data were processed using the test Wilcoxon obtained task rank values between pretest and posttest 2.0 23 with Asymp. Sig (2-tailed) 0.0 43 . Predetermined probability ? = 0.05. The alternative hypothesis is accepted because the probability <of the predetermined probability is 0.0 43 <0.05. So it is proven that the use of video tutorial models in improving makeup skills for mildly retarded children.